Sex-related differences in retinal function in Wistar rats: implications for toxicity and safety studies - Tyszkiewicz, Cheryl; Hwang, Seo-Kyoung; Manickam, Balasubramanian; Jakubczak, Ben; Walters, Karen M.; Bolt, Michael W.; Santos, Rosemary; Liu, Chang-Ning (Frontiers in Toxicology, 2023)
Introduction: Wistar Han rats are a preferred strain of rodents for general toxicology and safety pharmacology studies in drug development. In some of these studies, visual functional tests that assess for retinal toxicity are included as an additional endpoint. Although the influence of gender on human retinal function has been documented for more than 6 decades, preclinically it is still uncertain if there are differences in retinal function between naïve male and female Wistar Han rats. Methods: In this study, sex-related differences in the retinal function were quantified by analyzing electroretinography (ERG) in 7-9-week-old (n = 52 males and 51 females) and 21–23-week-old Wistar Han rats (n = 48 males and 51 females). Optokinetic tracking response, brainstem auditory evoked potential, ultrasonic vocalization and histology were tested and evaluated in a subset of animals to investigate the potential compensation mechanisms of spontaneous blindness. Results/Discussion: Absence of scotopic and photopic ERG responses was found in 13% of 7-9-week-old (7/52) and 19% of 21–23-week-old males (9/48), but none of female rats (0/51). The averaged amplitudes of rod- and cone-mediated ERG b-wave responses obtained from males were significantly smaller than the amplitudes of the same responses from age-matched females (−43% and −26%, respectively) at 7–9 weeks of age. There was no difference in the retinal and brain morphology, brainstem auditory responses, or ultrasonic vocalizations between the animals with normal and abnormal ERGs at 21–23 weeks of age. In summary, male Wistar Han rats had altered retinal responses, including a complete lack of responses to test flash stimuli (i.e., blindness), when compared with female rats at 7–9 and 21–23 weeks of age. Therefore, sex differences should be considered when using Wistar Han rats in toxicity and safety pharmacology studies with regards to data interpretation of retinal functional assessments.